SINTESIS POLI ASAM LAKTAT BERBOBOT MOLEKUL RENDAH MEMAKAI KATALIS STANNUM - Ricson P. Hutagaol; Lany Nurhayati; Jessica Analy (JURNAL SAINS NATURAL, 2011)
Synthesis Of Poly Lactic Acid Catalyst To Use Low-molecular-weight Using Stannum Catalyst           Poly lactic acid is a polyester that can be produced using raw materials of renewable natural resources such as starch and cellulose. These polymers can be degraded by hydrolysis process in the body and excreted within a few months. This polymer is not toxic and has been widely used in medical field such as for implants and medium in drug delivery systems (Drug Delivery System, DDS). Low molecular weight polymers that accelerate the degradation and the increasing concentration of drug detachment, while polymers with high molecular weight have a lower solubility so degraded more slowly. Polymerization process is affected by the solvent used, reaction temperature, time of agitation and catalyst used. Stanum (Sn) is the best catalyst is used to obtain polymers at relatively low temperatures. Synthesis is done by mixing the lactic acid with xylene and Stanum as a catalyst. Variation Stanum catalyst used, ie 0%, 1.0%, 2.0%, 3.0%, and 4.0%. Reacted in a reactor at a temperature of 140 ° C for 14 hours. Added chloroform, filtered and added to cold methanol. The precipitate was filtered and washed with cold methanol. The rst deposits exposed in the air and then heated in an oven at 80 ° C. Based on the results of the study, obtained the concentration of 2% was an optimum concentration of Sn is used to produce 4.55 grams of poly lactic acid of 20 grams of lactic acid with a molecular weight of 23289.83g/mol and the residue Stanum at 175.174 ppm. Keywords : Poly lactic acid, polikondensasu, catalyst, sanum.  ABSTRAK          Poli asam laktat merupakan poliester yang dapat diproduksi menggunakan bahan baku sumber daya alam terbarukan seperti pati dan selulosa. Polimer ini dapat terdegradasi dengan proses hidrolisis dalam tubuh dan terekskresi dalam waktu beberapa bulan. Polimer ini tidak meracuni tubuh dan telah banyak digunakan dalam bidang kedokteran seperti untuk implan dan medium dalam sistem penyampaian obat (Drug Delivery System, DDS). Bobot molekul polimer yang rendah mempercepat degradasi dan naiknya konsentrasi lepasan obat, sedangkan polimer dengan bobot molekul tinggi memiliki kelarutan yang lebih rendah sehingga terdegradasi lebih lambat. Proses polimerisasi dipengaruhi oleh pelarut yang digunakan, suhu reaksi, waktu pengocokan dan katalis yang digunakan. Stanum (Sn) merupakan katalis yang paling baik digunakan untuk mendapatkan polimer pada suhu yang relatif rendah. Sintesis dilakukan dengan mencampur asam laktat dengan xilena dan stanum sebagai katalis. Dilakukan variasi katalis stanum yang digunakan, yaitu    0 % ; 1,0 % ; 2,0 % ; 3,0 % ; dan 4,0 %. Direaksikan dalam reaktor pada suhu  140 °C selama 14 jam. Ditambahkan kloroform, disaring dan ditambahkan metanol dingin. Endapan disaring dan dicuci dengan metanol dingin. Sisa endapan dianginkan di udara lalu dipanaskan dalam oven pada suhu 80 °C. Berdasarkan hasil penelitian, didapat konsentrasi 2% merupakan konsentrasi Sn yang paling optimum digunakan untuk menghasilkan 4,55 gram poli asam laktat dari 20 gram asam laktat dengan bobot molekul 23289,83 g/mol dan residu stanum sebesar 175,174 ppm.Kata kunci : Poli asam laktat, polikondensasu, katalis, stanum.